Phylogeography Based on Mitochondrial DNA Reveals Large Genetic Differences within Eswatini's Eldana saccharina Populations - Mphumelelo Ndlovu; Sibusiso Sibandze; Bonginkosi Raymond Dlamini; Yoseph Assefa (Darul Yasin Al Sys, 2026)
The African sugarcane stalk borer, Eldana saccharina, is a widespread pest across sub-Saharan Africa and often exhibits substantial genetic structuring across its broad distribution, yet little is known about its genetic variation within the relatively small nation of Eswatini. This study employed mitochondrial cytochrome c oxidase subunit I (COI) gene sequencing to investigate the phylogeography of E. saccharina in sugarcane-producing areas of Eswatini. Analysis of 69 specimens revealed two distinct genetic groups with significant genetic differentiation, despite the limited geographic scale of sampling. A minimum spanning network and a maximum parsimony tree clearly demonstrated the separation of the population into two discrete lineages. The observed genetic differences are likely shaped by the pest’s specialization on different host plants and historical biogeographic processes. This work provides the first DNA-based characterization of E. saccharina in Eswatini and the first report on the phylogeography of its populations in the country. The dataset generated constitutes a valuable addition to existing E. saccharina taxonomic resources and will support more rapid and informed decision making in the design and implementation of biological control programs in Eswatini and across the African continent.